2006
DOI: 10.1086/509704
|View full text |Cite
|
Sign up to set email alerts
|

Powerful Multilocus Tests of Genetic Association in the Presence of Gene-Gene and Gene-Environment Interactions

Abstract: In modern genetic epidemiology studies, the association between the disease and a genomic region, such as a candidate gene, is often investigated using multiple SNPs. We propose a multilocus test of genetic association that can account for genetic effects that might be modified by variants in other genes or by environmental factors. We consider use of the venerable and parsimonious Tukey's 1-degree-of-freedom model of interaction, which is natural when individual SNPs within a gene are associated with disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
183
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(185 citation statements)
references
References 34 publications
2
183
0
Order By: Relevance
“…We note that there exist gene-based methods that jointly test for the main effect and the interaction effect. 23,24 Although the goals of these tests are slightly different from ours, they all aim to incorporate information contributed by multiple markers in a gene. How to extend the proposed PC framework to jointly test for the main and interaction effects would merit further research.…”
Section: Discussionmentioning
confidence: 99%
“…We note that there exist gene-based methods that jointly test for the main effect and the interaction effect. 23,24 Although the goals of these tests are slightly different from ours, they all aim to incorporate information contributed by multiple markers in a gene. How to extend the proposed PC framework to jointly test for the main and interaction effects would merit further research.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the effects of genes (SNPs) and covariates on the selected disease trait are often described through a multivariate linear or generalized linear model. Through a set of latent biological phenotypes, Chatterjee et al [5] described a conceptual framework for modeling genetic associations and gene-gene and gene-environment interactions in indirect-association studies with multivariate logistic regression models. Maity et al [6] extended the approaches proposed by Chatterjee et al [5] to studies with repeated measures data and developed a class of score tests in general semi-parametric regression models.…”
Section: Introductionmentioning
confidence: 99%
“…They are the third generation genetic markers in humans and play an important role in identifying disease-related genes, elucidating phenotypic differences among individuals, and interpreting disease susceptibilities in different populations and individuals. Previous studies have shown that the genesis and development of complicated diseases are not completely caused by genetic factors; rather, they are results of the interactions between genetic variations and environmental factors (Chatterjee et al, 2006;Wong et al, 2010). It is likely that there is only weak relevance, but not a major genetic effect between every individual gene and disease.…”
Section: Introductionmentioning
confidence: 99%